PENERAPAN MODEL PEMBELAJARAN PROJEK BASED LEARNING (PjBL) BERBASIS TPaCK - Rochmadi, Nur Wahyu; Rochastuti, Larasati (Prosiding Temu Ilmiah Nasional Guru, 2023)
the quality of human resources are increasing, not only must they be knowledgeable, skilled and have character, but they must also be productive (productive), suitable for publication and profitable. These conditions create a learning model that requires students to produce "something" that is worthy of publication and profitable for teachers to practice. One of them is the project-based learning model (PjBL), because PjBL requires students to do something or create something to solve a problem. The application of the project-based learning model in the field of civics requires the capability of knowledge and skills to produce something based on empathy and civic responsibility to participate in resolving various civic problems that occur in the surrounding environment. The process of implementing the PjBL learning model based on TPaCK is one of the models in PPKn learning, known as a citizenship project, and improve civic intelligence, civic skills, civic responsibility and civic participation students' capabilities, as well as the quality of their learning.